Evidence for an antihypertensive effect of a land snail (Helix aspersa) by-product hydrolysate – Identification of involved peptides. (April 2016) - Cudennec, Benoit; Violle, Nicolas; Chataigné, Gabrielle; Drevet, Pascal; Bisson, Jean-François; Dhulster, Pascal; Ravallec, Rozenn
Highlights: ACE inhibitory activity of SBH was characterised by an IC50 value of 23 µg⋅mL −1 . Five of the identified peptides in the active fraction are well known ACE inhibitors. SBH stimulated intestinal cell metabolism and was not toxic for Wistar Rats. SBH significantly reduced systolic blood pressure in SHR rats. This snail by-product hydrolysate could be valorised as an antihypertensive ingredient. Abstract: The antihypertensive potential of a land snail by-product hydrolysate (SBH), obtained after an industrial treatment of the raw material, was studied in vitro and in vivo . The ACE inhibitory activity of SBH was characterised by an IC50 value of 23 µg⋅mL −1, which was not affected by in vitro digestion. SBH enhanced the Caco-2 intestinal cell metabolic activity and did not induce any toxicity in Wistar rats. The partial purification of SBH led to the obtainment of an active fraction characterised by an IC50 of 0.007 µg⋅mL −1 . The sequences of the 17 most abundant peptides of the fraction were identified by LC/MS/MS analysis. Seven of them (YG, YA, VY, SF, FG, GF and VW) are known ACE inhibitory peptides. Finally, in vivo study on SHR rats showed that SBH significantly reduced systolic blood pressure. SBH represents therefore a new candidate as an ingredient for the design of functional foods against hypertension.